Composite resin-based hard carbon negative electrode material for sodium ion battery and preparation method of composite resin-based hard carbon negative electrode material
By introducing modified lignin and modified crosslinking agent into the composite resin-based hard carbon anode material for sodium ion batteries, the problem of insufficient electrochemical performance and cyclic stability of existing materials is solved, and higher structural stability and electrochemical performance are achieved, while reducing costs and toxic gas release in production.
Patent Information
- Application Number
- CN202411990776.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
The electrochemical performance and cyclic stability of the existing composite resin-based hard carbon anode materials for sodium ion batteries need to be improved and the cost is relatively high.
Modified composite resin-based hard carbon material is used to replace part of phenol by introducing modified lignin and using modified crosslinking agent acrylate compounds to improve the structural stability, conductivity and cyclic properties of the material.
The structural stability, electrochemical performance and cycle stability of composite resin-based hard carbon anode material for sodium ion batteries are improved, production costs are reduced, and safety and environmental protection of industrial production are improved.
Smart Images

Figure CN119725493A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of negative electrode material processing, and in particular to a composite resin-based hard carbon negative electrode material for a sodium ion battery and a preparation method thereof. Background Art
[0002] Among various LIBs alternative energy storage technologies, sodium-ion batteries (SIBs) have attracted great attention due to their low cost, high sodium resources, and low carbon footprint.
[0003] Uniform distribution, relatively high energy density and similar working principle to LIB have been widely studied, especially in the fields of large-scale energy storage and slow transportation, and have become a candidate energy storage technology that is expected to partially replace LIB. For large batteries, the most important considerations are chemical properties, stability and cost. Therefore, the key to the development of SIBs is to reduce costs as much as possible while improving excellent electrochemical performance. Therefore, it is particularly important to develop novel high-performance and low-cost commercial materials for sodium-ion batteries.
[0004] In the prior art, phenolic resin is a commonly used hard carbon negative electrode material in sodium ion batteries and has good power storage capacity. However, when the phenolic resin undergoes a condensation reaction, there are too few sites for phenol and formaldehyde to generate hydroxymethyl groups, and the cross-linking reaction is insufficient, resulting in a low degree of cross-linking and a loose structure of the phenolic resin. As a result, the electrochemical performance and efficiency of the sodium ion battery need to be further improved. In addition, after curing, the phenolic resin lacks sufficient softness and is relatively brittle. After multiple cycles of use, the internal stress accumulation of the sodium ion battery negative electrode material is too large, resulting in poor cycle stability of the sodium ion battery negative electrode material.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a composite resin-based hard carbon negative electrode material for sodium ion batteries and a preparation method thereof, so as to solve the problem that the electrochemical performance and cycle stability of the composite resin-based hard carbon negative electrode material for sodium ion batteries in the prior art need to be further improved.
[0007] The purpose of the present invention can be achieved by the following technical scheme: a composite resin-based hard carbon negative electrode material for a sodium ion battery comprises the following components in parts by weight: 70-80 parts of a modified composite resin-based hard carbon material, 7-10 parts of a conductive agent, 4-7 parts of a modified cross-linking agent and 5-10 parts of a solvent.
[0008] Furthermore, the conductive agent is one or more of acetylene black, carbon fiber and carbon nanotube; and the solvent is methanol.
[0009] Furthermore, the preparation method of the modified composite resin-based hard carbon material comprises the following steps:
[0010] A1. Place the modified lignin, phenol solution and sodium hydroxide solution in a reactor at 90°C and stir for 15 minutes to mix evenly, add formaldehyde solution, and keep the mixture at 90°C for 2.5 hours to obtain a mixed solution;
[0011] A2, mixing the mixed solution of step A1 and deionized water uniformly, preparing polymer microspheres by spray drying, and post-treating to obtain a modified composite resin-based precursor;
[0012] A3. Heat and calcine the modified composite resin-based precursor to obtain a sodium ion composite resin-based hard carbon negative electrode material.
[0013] Furthermore, in step A1, the concentration of the phenol solution is 5.0 mol / L, the concentration of the sodium hydroxide solution is 13.0 mol / L, the concentration of the formaldehyde solution is 17.0 mol / L, and the dosage ratio of the modified lignin, the phenol solution, the sodium hydroxide solution and the formaldehyde solution is 0.3 g: 0.2 mL: 0.2 mL: 1.5 mL.
[0014] Furthermore, the preparation method of the modified lignin described in step A1 comprises the following steps:
[0015] B1, placing sodium hydroxide solution and corn sugar residue in a reactor heated to 150-160° C. and stirring for 90 minutes, adding hydrochloric acid solution for pickling, centrifuging and precipitating, and drying the solid to obtain composite lignin;
[0016] B2. Place the composite lignin and acetone solution in a reactor at 25-30°C and stir for 12 hours. Centrifuge to remove insoluble precipitates and freeze-dry the supernatant to obtain modified lignin.
[0017] Furthermore, the concentration of the sodium hydroxide solution in step B1 is 2.5 mol / L, the concentration of the hydrochloric acid solution is 12.9 mol / L, the amount ratio of the sodium hydroxide solution, corn sugar residue and hydrochloric acid solution is 10 mL: 1.0 g: 5 mL, the concentration of the acetone solution in step B2 is 6.0 mol / L, and the amount ratio of the composite lignin and the acetone solution is 1 g: 10 mL; the volume ratio of the mixed solution and deionized water in step A2 is 0.3: 10, and the post-treatment step includes: delivering the polymer microsphere solution to the nozzle at a speed of 400 mL / h through a jet pump, and atomizing at a pressure of 250 Pa, the temperature of the inlet air is stabilized at 120-150°C, the temperature of the outlet air is stabilized at 50-80°C, and curing at 150°C-200°C for 20 h to obtain a modified composite resin-based precursor.
[0018] Furthermore, the heating and calcining method described in step A3 is: placing the modified composite resin-based precursor in a tubular furnace with an argon atmosphere, heating the temperature from room temperature to 400°C at a heating rate of 2°C / min, keeping the temperature for 2 hours, then heating the temperature from 500°C to 1200°C at a heating rate of 5°C / min and keeping the temperature for 6 hours, and cooling to room temperature to obtain a sodium ion composite resin-based hard carbon negative electrode material.
[0019] Furthermore, the preparation method of the modified cross-linking agent comprises the following steps:
[0020] C1. Prepare a mixed monomer from butyl acrylate, styrene, acrylic acid and β-hydroxyethyl methacrylate for later use;
[0021] C2. Add the emulsion and the mixed monomers into the reactor and stir. The temperature of the reactor is raised to 75-85°C. The catalyst is added dropwise into the reactor and the reaction is carried out for 5 hours at a temperature preservation temperature. After cooling, the mixture is centrifuged and filtered to obtain the modified cross-linking agent.
[0022] Furthermore, the amount ratio of butyl acrylate, styrene, acrylic acid and β-hydroxyethyl methacrylate in step C1 is 15.8g:18.0g:1.0g:1.0g, the amount ratio of the emulsion, mixed monomer and catalyst in step C2 is 12.0g:1.2g:1.0g, the concentration of the catalyst solution is 0.08mol / L potassium persulfate solution, and the emulsion in step C2 is composed of methanol, dipropylene glycol dimethyl ether, sodium dodecylbenzene sulfonate and pingpingjia O-9 in a weight ratio of 50.0:1.0:0.3:0.3.
[0023] Furthermore, a method for preparing a composite resin-based hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0024] S1, mixing and grinding the modified composite resin-based hard carbon negative electrode material, the conductive agent, and the modified cross-linking agent, and passing through an 800-mesh sieve to obtain a mixture;
[0025] S2. Mix the mixture and deionized water, and continue stirring for 8 hours to obtain a uniform coating slurry. Evenly coat the coating slurry on aluminum foil, place it in a vacuum drying oven at 80° C. and dry it for 12 hours. Cut it to obtain a negative electrode material.
[0026] The present invention has the following beneficial effects:
[0027] 1. The composite resin-based hard carbon negative electrode material for sodium ion batteries of the present invention is prepared by modifying the phenolic resin-based material and introducing modified lignin to replace part of the phenol, so that the further carbonized composite resin-based hard carbon material has higher structural stability, conductivity, mechanical strength and cycle performance, and reduces the release of toxic substances produced in the preparation process, thereby improving the safety and environmental protection of industrial production; the modified cross-linking agent acrylate compound itself has better adhesion and flexibility, which can further improve the cycle stability, rate performance and environmental protection of the composite resin-based hard carbon negative electrode material for sodium ion batteries; at the same time, the modified cross-linking agent can make the composite resin-based hard carbon material better mixed and cured with other battery materials, so that the sodium ion battery has a more stable structure and more efficient electrochemical performance.
[0028] 2. In the process of preparing composite resin-based hard carbon negative electrode materials for sodium ion batteries, the present invention introduces modified lignin to replace part of the phenol in the synthesis of phenolic resin, so that more sites of the ortho-position of the phenolic hydroxyl group in the reaction are exposed, which is beneficial to the formation of hydroxymethyl groups, improves the degree of cross-linking reaction, improves structural stability, and further enhances the cycle stability, electrochemical properties and chemical tolerance of composite resin-based hard carbon negative electrode materials for sodium ion batteries. Since phenol is toxic, the introduction of modified lignin can also reduce the release of toxic gases in the preparation and application of composite resin-based hard carbon negative electrode materials for sodium ion batteries, thereby improving safety. Lignin is widely available and inexpensive, which further reduces production costs.
[0029] 3. In the process of preparing composite resin-based hard carbon negative electrode materials for sodium ion batteries, the present invention uses a modified cross-linking agent to enhance the electrochemical properties and cycle stability of sodium ion batteries. The main component of the modified cross-linking agent is an acrylate substance. Compared with the traditional cross-linking agent composed of polyvinylidene fluoride and N-methylpyrrolidone, it has stronger adhesion, bonding strength, structural stability and toughness, so that the rate performance, cycle stability and conductivity of the prepared composite resin-based hard carbon negative electrode material for sodium ion batteries are further improved. The solvent used in combination with the modified cross-linking agent is methanol, which has the advantages of reducing toxicity and reducing the problem of solvent residue, thereby improving the safety of the composite resin-based hard carbon negative electrode material for sodium ion batteries during preparation and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1This is a TEM image of the composite resin-based hard carbon negative electrode material for sodium ion batteries in Example 2 of the present invention;
[0032] Figure 2 This is a SEM image of the composite resin-based hard carbon negative electrode material for sodium ion battery in Example 2 of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The corn sugar residue used in the present invention is obtained from Huamo Biotechnology Co., Ltd., and its main component is crude protein.
[0035] Example 1
[0036] This embodiment provides a method for preparing a composite resin-based hard carbon negative electrode material for a sodium ion battery, comprising the following steps:
[0037] S1. Preparation of sodium ion composite resin-based hard carbon
[0038] Weigh: 10.0 g corn sugar residue and 100 mL sodium hydroxide solution, place in a three-necked flask heated to 150° C. and stir for 90 min, add hydrochloric acid solution for acid washing, centrifuge and precipitate, and dry the solid to obtain composite lignin;
[0039] Weigh: 6.3 g of composite lignin and 60 mL of acetone solution were placed in a reactor at 30°C and stirred for 12 h. Insoluble precipitates were removed by centrifugation, and the supernatant was freeze-dried to obtain modified lignin for later use;
[0040] Weigh: 5.5 g of modified lignin, 20 mL of phenol solution and 20 mL of sodium hydroxide solution, place them in a three-necked flask at 92 ° C and stir for 15 min to mix evenly, add 30 mL of formaldehyde solution, keep warm at 90 ° C for reaction for 2.5 h to obtain a mixed solution, mix the mixed solution with 400 mL of deionized water, prepare polymer microspheres using a spray dryer, transport the polymer microsphere solution to the nozzle at a speed of 400 mL / h through a jet pump, and atomize at a pressure of 250 Pa. The temperature of the inlet air is stabilized at 130 ° C, and the temperature of the outlet air is stabilized at 60 ° C. Curing at 150 ° C for 20 h to obtain a modified composite resin-based precursor.
[0041] Weigh: 6.2 g of modified composite resin-based precursor, place it in a tubular furnace in an argon atmosphere, increase the temperature from room temperature to 400°C at a heating rate of 2°C / min, keep it warm for 2 hours, then increase the temperature from 500°C to 1200°C at a heating rate of 5°C / min and keep it warm for 6 hours. After cooling to room temperature, 3.5 g of modified sodium ion composite resin-based hard carbon negative electrode material is obtained.
[0042] S2. Preparation of modified crosslinking agent
[0043] Weigh: 1.6 g of butyl acrylate, 1.8 g of styrene, 0.1 g of acrylic acid and 0.1 g of β-hydroxyethyl methacrylate to prepare a mixed monomer for later use;
[0044] Weigh: 0.01 g of potassium persulfate and 3.5 g of deionized water to prepare a catalyst for later use;
[0045] Weigh: 5.0g methanol, 0.1g dipropylene glycol dimethyl ether, 0.03g sodium dodecylbenzene sulfonate and 0.3g Pingpingjia O-9 and put them in a three-necked flask, slowly add the mixed monomers dropwise, raise the temperature to 50°C, add the catalyst dropwise into the three-necked flask, keep the reaction warm for 5h, cool and centrifuge to precipitate, and filter to obtain the modified cross-linking agent.
[0046] S3. Preparation of composite resin-based hard carbon negative electrode for sodium ion battery
[0047] Weigh: 3.5 g of modified composite resin-based hard carbon negative electrode material, 0.4 g of acetylene black, and 0.4 g of modified cross-linking agent, mix and grind, and pass through an 800-mesh sieve to obtain a mixture;
[0048] The mixture was mixed with 1.2 mL of deionized water and stirred for 8 h to obtain a uniform coating slurry. The coating slurry was evenly coated on aluminum foil, dried in a vacuum drying oven at 80° C. for 12 h, and cut to obtain a negative electrode material.
[0049] Example 2
[0050] This embodiment provides a method for preparing a composite resin-based hard carbon negative electrode material for a sodium ion battery, comprising the following steps:
[0051] S1. Preparation of sodium ion composite resin-based hard carbon
[0052] Weigh: 12.0 g corn sugar residue and 120 mL sodium hydroxide solution, place in a three-necked flask heated to 150°C and stir for 90 min, add hydrochloric acid solution for acid washing, centrifuge and precipitate, dry the solid to obtain 8.0 g of composite lignin;
[0053] Weigh: 8.0 g of composite lignin and 80 mL of acetone solution were placed in a reactor at 30° C. and stirred for 12 h. Insoluble precipitates were removed by centrifugation. The supernatant was freeze-dried to obtain modified lignin for later use.
[0054] Weigh: 7.5 g of modified lignin, 35 mL of phenol solution and 35 mL of sodium hydroxide solution, place in a three-necked flask at 92 ° C and stir for 15 min to mix evenly, add 40 mL of formaldehyde solution, keep at 90 ° C for reaction for 2.5 h to obtain a mixed solution, mix the mixed solution and 530 mL of deionized water evenly, use a spray dryer to prepare polymer microspheres, deliver the polymer microsphere solution to the nozzle through a jet pump at a speed of 400 mL / h, and atomize at a pressure of 250 Pa. The temperature of the inlet air is stabilized at 130 ° C, and the temperature of the outlet air is stabilized at 60 ° C. Curing at 150 ° C for 20 h to obtain a modified composite resin-based precursor;
[0055] Weigh: 7.1 g of modified composite resin-based precursor, place it in a tubular furnace in an argon atmosphere, increase the temperature from room temperature to 400°C at a heating rate of 2°C / min, keep it warm for 2 hours, then increase the temperature from 500°C to 1200°C at a heating rate of 5°C / min and keep it warm for 6 hours. After cooling to room temperature, a modified sodium ion composite resin-based hard carbon negative electrode material is obtained.
[0056] S2. Preparation of modified crosslinking agent
[0057] Weigh: 2.1 g of butyl acrylate, 2.4 g of styrene, 0.1 g of acrylic acid and 0.1 g of β-hydroxyethyl methacrylate to prepare a mixed monomer for later use;
[0058] Weigh: 0.01 g potassium persulfate and 3.5 g deionized water to prepare a catalyst solution for later use;
[0059] Weigh: 6.7g methanol, 0.1g dipropylene glycol dimethyl ether, 0.04g sodium dodecylbenzene sulfonate, 0.4g peregal O-9 and 0.01g potassium persulfate, put them in a three-necked flask, slowly add the mixed monomers dropwise, raise the temperature to 50°C, add the catalyst dropwise into the three-necked flask, keep the reaction warm for 5h, cool and centrifuge to precipitate, and filter to obtain the modified cross-linking agent.
[0060] S3. Preparation of composite resin-based hard carbon negative electrode for sodium ion battery
[0061] Weigh: 5.6 g of modified composite resin-based hard carbon negative electrode material, 0.5 g of acetylene black, and 0.7 g of modified cross-linking agent, mix and grind, and pass through an 800-mesh sieve to obtain a mixture;
[0062] The mixture was mixed with 1.6 mL of deionized water and stirred for 8 h to obtain a uniform coating slurry. The coating slurry was evenly coated on aluminum foil, dried in a vacuum drying oven at 80° C. for 12 h, and cut to obtain a negative electrode material.
[0063] Example 3
[0064] This embodiment provides a method for preparing a composite resin-based hard carbon negative electrode material for a sodium ion battery, comprising the following steps:
[0065] S1. Preparation of sodium ion composite resin-based hard carbon
[0066] Weigh: 15.0 g corn sugar residue and 100 mL sodium hydroxide solution, place in a three-necked flask heated to 150°C and stir for 90 min, add hydrochloric acid solution for acid washing, centrifuge and precipitate, and dry the solid to obtain 10.5 g of composite lignin;
[0067] Weigh: 10.5 g of composite lignin and 110 mL of acetone solution were placed in a reactor at 30°C and stirred for 12 h. Insoluble precipitates were removed by centrifugation, and the supernatant was freeze-dried to obtain modified lignin for later use;
[0068] Weigh: 10.5 g of modified lignin, 50 mL of phenol solution and 50 mL of sodium hydroxide solution, place in a three-necked flask at 92 ° C and stir for 15 min to mix evenly, add 60 mL of formaldehyde solution, keep at 90 ° C for reaction for 2.5 h to obtain a mixed solution, mix the mixed solution and 450 mL of deionized water evenly, use a spray dryer to prepare polymer microspheres, deliver the polymer microsphere solution to the nozzle through a jet pump at a speed of 400 mL / h, and atomize at a pressure of 250 Pa. The temperature of the inlet air is stabilized at 130 ° C, and the temperature of the outlet air is stabilized at 60 ° C. Curing at 150 ° C for 20 h to obtain a modified composite resin-based precursor;
[0069] Weigh: 8.2 g of modified composite resin-based precursor, place it in a tubular furnace in an argon atmosphere, increase the temperature from room temperature to 400°C at a heating rate of 2°C / min, keep it warm for 2 hours, then increase the temperature from 500°C to 1200°C at a heating rate of 5°C / min and keep it warm for 6 hours. After cooling to room temperature, a modified sodium ion composite resin-based hard carbon negative electrode material is obtained.
[0070] S2. Preparation of modified crosslinking agent
[0071] Weigh: 1.8 g butyl acrylate, 2.1 g styrene, 0.1 g acrylic acid and 0.1 g β-hydroxyethyl methacrylate to prepare a mixed monomer for later use;
[0072] Weigh: 0.01 g potassium persulfate and 3.5 g deionized water to prepare a catalyst solution for later use;
[0073] Weigh: 8.0g methanol, 0.1g dipropylene glycol dimethyl ether, 0.03g sodium dodecylbenzene sulfonate, 0.3g peregal O-9 and 0.01g potassium persulfate, put them in a three-necked flask, slowly add the mixed monomers dropwise, raise the temperature to 50°C, add the catalyst solution dropwise to the three-necked flask, keep the reaction warm for 5h, cool and filter to obtain the modified cross-linking agent.
[0074] S3. Preparation of composite resin-based hard carbon negative electrode for sodium ion battery
[0075] Weigh: 6.4 g of modified composite resin-based hard carbon negative electrode material, 0.4 g of acetylene black, and 0.4 g of modified cross-linking agent, mix and grind, and pass through an 800-mesh sieve to obtain a mixture;
[0076] The mixture was mixed with 1.4 mL of deionized water and stirred for 8 h to obtain a uniform coating slurry. The coating slurry was evenly coated on aluminum foil, dried in a vacuum drying oven at 80° C. for 12 h, and cut to obtain electrode sheets.
[0077] Comparative Example 1
[0078] The difference between this comparative example and Example 3 is that step S1 is eliminated, and the modified sodium ion composite resin-based hard carbon negative electrode material in step S3 is replaced by an equal amount of phenolic resin-based hard carbon negative electrode material.
[0079] Comparative Example 2
[0080] The difference between this comparative example and Example 3 is that step S2 is eliminated and the medium-modified cross-linking agent in step S3 is replaced by an equal amount of polyvinylidene fluoride.
[0081] Comparative Example 3
[0082] The difference between this comparative example and Example 3 is that in step S1, the acetone solution is not used to modify the lignin.
[0083] Performance testing:
[0084] The chemical properties, stability and conductivity of the composite resin-based hard carbon negative electrode materials for sodium ion batteries prepared in Examples 1-3 and Comparative Examples 1-3 were tested, wherein the chemical properties were measured according to the standard SJ / T 11793-2022 "Test Method for Electrochemical Properties of Electrode Materials for Ion Batteries", the conductivity was measured according to the standard SJ / T 11792-2022 "Test Method for Conductivity of Electrode Materials for Lithium Ion Batteries", and the thermal stability was measured according to GB / T 2423.2-2008 "Environmental Testing for Electrical and Electronic Products". The specific test results of the standards are shown in Table 1:
[0085] Table 1-Performance test data of the sample
[0086] Data Analysis:
[0087] By comparing and analyzing the data of Examples 1-3 and Comparative Examples 1-3, the rate performance of the composite resin-based hard carbon negative electrode material for sodium ion batteries prepared by the present invention is improved to 93.3%, the cycle stability is 85.4%, the charge and discharge performance is improved to 154.9 mAh / g, the coulomb efficiency is 92.3 mAh / g and the conductivity is improved to 0.023 S / cm, and all performance parameters are better than those of the comparative example.
[0088] Compared with Examples 1-3, the rate performance, cycle stability, charge and discharge performance, Coulomb efficiency and conductivity of Comparative Example 1 are all reduced, indicating that the modification of the composite resin-based precursor can effectively improve the structural stability and chemical tolerance of the composite resin-based hard carbon material for sodium ion batteries, thereby improving its electrochemical performance.
[0089] Compared with Examples 1-3, the charge and discharge performance and coulomb efficiency of Comparative Example 2 are basically the same, while the rate performance, cycle stability and conductivity are significantly reduced, indicating that the modification of the cross-linking agent can effectively improve the adhesion and cross-linking degree of the composite resin-based hard carbon material for sodium ion batteries, thereby improving its electrochemical performance.
[0090] Compared with Examples 1-3, the rate performance, cycle stability, charge and discharge performance, coulombic efficiency and conductivity of Comparative Example 3 are all reduced, indicating that the use of acetone solution to grade the composite lignin can reduce the generation of side reactions in the synthesis of phenolic resin, unify the structure of the composite resin-based hard carbon material for sodium ion batteries, and effectively improve the structural stability of the composite resin-based hard carbon material for sodium ion batteries, thereby improving its electrochemical performance.
[0091] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A composite resin-based hard carbon negative electrode material for sodium ion batteries, characterized in that: The invention comprises the following components in parts by weight: 70-80 parts of modified composite resin-based hard carbon material, 7-10 parts of conductive agent, 4-7 parts of modified cross-linking agent and 5-10 parts of solvent.
2. The composite resin-based hard carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: The conductive agent is one or more of acetylene black, carbon fiber and carbon nanotube; and the solvent is methanol.
3. The composite resin-based hard carbon negative electrode material for sodium ion battery according to claim 1, characterized in that: The method for preparing the modified composite resin-based hard carbon material comprises the following steps: A1. Place the modified lignin, phenol solution and sodium hydroxide solution in a reactor at 90-100°C and stir for 15 minutes to mix evenly, add formaldehyde solution, and keep the mixture at 90-100°C for 2.5 hours to obtain a mixed solution; A2, mixing the mixed solution of step A1 and deionized water uniformly, preparing polymer microspheres by spray drying, and post-treating to obtain a modified composite resin-based precursor; A3. Heat and calcine the modified composite resin-based precursor to obtain a sodium ion composite resin-based hard carbon negative electrode material.
4. The composite resin-based hard carbon negative electrode material for sodium ion battery according to claim 3, characterized in that: In step A1, the concentration of the phenol solution is 5.0 mol / L, the concentration of the sodium hydroxide solution is 13.0 mol / L, the concentration of the formaldehyde solution is 17.0 mol / L, and the amount ratio of the modified lignin, the phenol solution, the sodium hydroxide solution and the formaldehyde solution is 0.3 g: 0.2 mL: 0.2 mL: 1.5 mL; In step A2, the volume ratio of the mixed solution to deionized water is 0.3:10, and the post-treatment step includes: delivering the polymer microsphere solution to the nozzle through a jet pump at a speed of 400 mL / h, and atomizing at a pressure of 250-300 Pa, stabilizing the temperature of the inlet air at 120-150°C, stabilizing the temperature of the outlet air at 50-80°C, and curing at 150°C-200°C for 20 h to obtain a modified composite resin-based precursor.
5. The composite resin-based hard carbon negative electrode material for sodium ion battery according to claim 3, characterized in that: In step A3, the heating and calcining method is: placing the modified composite resin-based precursor in a tubular furnace with an argon atmosphere, heating the temperature from room temperature to 400-500°C at a heating rate of 2°C / min, keeping the temperature for reaction for 2 hours, then heating the temperature from 500°C to 1200-1300°C at a heating rate of 5°C / min and keeping the temperature for 6 hours, and cooling to room temperature to obtain a sodium ion composite resin-based hard carbon negative electrode material.
6. The composite resin-based hard carbon negative electrode material for sodium ion batteries according to claim 3, characterized in that: The preparation method of modified lignin comprises the following steps: B1, placing sodium hydroxide solution and corn sugar residue in a reactor heated to 150-160° C. and stirring for 90 minutes, adding hydrochloric acid solution for pickling, centrifuging and precipitating, and drying the solid to obtain composite lignin; B2. Place the composite lignin and acetone solution in a reactor at 25-30°C and stir for 12 hours. Centrifuge to remove insoluble precipitates and freeze-dry the supernatant to obtain modified lignin.
7. The composite resin-based hard carbon negative electrode material for sodium ion batteries according to claim 6, characterized in that: In step B1, the concentration of the sodium hydroxide solution is 2.5 mol / L, the concentration of the hydrochloric acid solution is 12.9 mol / L, and the dosage ratio of the sodium hydroxide solution, corn sugar residue and hydrochloric acid solution is 10 mL: 1.0 g: 5 mL; in step B2, the concentration of the acetone solution is 6.0 mol / L, and the dosage ratio of the composite lignin and the acetone solution is 1 g: 10 mL.
8. The composite resin-based hard carbon negative electrode material for sodium ion batteries according to claim 1, characterized in that: The preparation method of the modified crosslinking agent comprises the following steps: C1. Prepare a mixed monomer from butyl acrylate, styrene, acrylic acid and β-hydroxyethyl methacrylate for later use; C2. Add the emulsion and the mixed monomers into the reactor and stir. The temperature of the reactor is raised to 75-85°C. The catalyst solution is added dropwise into the reactor. The reaction is kept warm for 5 hours. After cooling, the mixture is centrifuged and filtered to obtain the modified cross-linking agent.
9. The composite resin-based hard carbon negative electrode material for sodium ion batteries according to claim 8, characterized in that: In step C1, the weight ratio of butyl acrylate, styrene, acrylic acid and β-hydroxyethyl methacrylate is 15.8g:18.0g:1.0g:1.0g; in step C2, the weight ratio of the emulsion, the mixed monomer and the catalyst is 12.0:1.2:1.0, the catalyst is a potassium persulfate solution with a concentration of 0.08mol / L, and the emulsion is composed of methanol, dipropylene glycol dimethyl ether, sodium dodecylbenzene sulfonate and pyroxacin O-9 in a weight ratio of 50.0:1.0:0.3:0.
3.
10. The method for preparing a composite resin-based hard carbon negative electrode material for a sodium ion battery according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing and grinding the modified composite resin-based hard carbon negative electrode material, the conductive agent, and the modified cross-linking agent, and passing through an 800-mesh sieve to obtain a mixture; S2. Mix the mixture and deionized water, and continue stirring for 8 hours to obtain a uniform coating slurry. Evenly coat the coating slurry on aluminum foil, place it in a vacuum drying oven at 80° C. and dry it for 12 hours. Cut it to obtain a negative electrode material.
Citation Information
Cited By
Hard carbon negative electrode material and preparation method and application thereof
CN119905585A
Hard carbon material coated with conductive polymer coating, preparation method of hard carbon material, negative plate and sodium ion battery
CN120727803A